Phosphonic acid adsorption on α-Bi2O3 surfaces - Bocchini, Adriana; Kollmann, S.; Gerstmann, Uwe; Schmidt, Wolf Gero; Grundmeier, Guido (Surface Science)

Microscopic origin of gray tracks in KTiOPO4 - Bocchini, Adriana; Gerstmann, Uwe; Schmidt, Wolf Gero (Physical Review B)

Mg dopants in lithium niobate: Defect models and impact on domain inversion - Bocchini, Adriana; Rüsing, Michael; Bollmers, Laura; Lengeling, Sebastian; Mues, Philipp; Padberg, Laura; Gerstmann, Uwe; Silberhorn, Christine; Eigner, Christof; Schmidt, Wolf Gero (Physical Review Materials)

Structural and Electrochemical Properties of F-Doped RbTiOPO4 (RTP:F) Predicted from First Principles - Bocchini, Adriana; Xie, Yingjie; Schmidt, Wolf Gero; Gerstmann, Uwe (Crystals)
Batteries based on heavier alkali ions are considered promising candidates to substitute for current Li-based technologies. In this theoretical study, we characterize the structural properties of a novel material, i.e., F-doped RbTiOPO4 (RbTiPO4F, RTP:F), and discuss aspects of its electrochemical performance in Rb-ion batteries (RIBs) using density functional theory (DFT). According to our calculations, RTP:F is expected to retain the so-called KTiOPO4 (KTP)-type structure, with lattice parameters of 13.236 Å, 6.616 Å, and 10.945 Å. Due to the doping with F, the crystal features eight extra electrons per unit cell, whereby each of these electrons is trapped by one of the surrounding Ti atoms in the cell. Notably, the ground state of the system corresponds to a ferromagnetic spin configuration (i.e., S=4). The deintercalation of Rb leads to the oxidation of the Ti atoms in the cell (i.e., from Ti3+ to Ti4+) and to reduced magnetic moments. The material promises interesting electrochemical properties for the cathode: rather high average voltages above 2.8 V and modest volume shrinkages below 13% even in the fully deintercalated case are predicted.

Rutile, anatase, brookite and titania thin film from Hubbard corrected and hybrid DFT - Badalov, Sabuhi; Bocchini, Adriana; Wilhelm, Rene; Kozub, A. L.; Gerstmann, Uwe; Schmidt, Wolf Gero (Materials Research Express)
As a benchmark, the structural, electronic and optical properties of the three main phases of TiO$\rm{_2}$ crystals have been calculated using Hubbard U correction and hybrid functional methods in density-functional theory. These calculations are compared concerning the available experimental observations on pristine TiO$\rm{_2}$ crystals. Modified hybrid functionals, particularly the PBE0 functional with 11.4% fraction of exact exchange, are shown to provide highly accurate atomic structures and also accurate electronic structure data, including optical excitation energies. With $\rm{DFT+U}$, accurate optical spectra are also possible, but only if the Hubbard U is applied on the O $\rm2p$ electrons exclusively. Furthermore, both methods, the 11.4%-PBE0 hybrid functional and the $\rm{DFT+U_p}$ scheme have been used to study TiO$\rm{_2}$ amorphous ultra-thin films, confirming the agreement of the two methods even with respect to small details of the optical spectra. Our results show that the proposed $\rm{DFT+U_p}$ methodology is computationally efficient, but still accurate. It can be applied to well-ordered TiO$\rm{_2}$ polymorphs as well as to amorphous TiO$\rm{_2}$ and will allow for the calculations of complex titania-based structures.

Potassium Titanyl Phosphate Material Engineering Boosting Integrated Optical Source Performance - Eigner, Christof; Padberg, Laura; Quiring, Viktor; Bocchini, Adriana; Santandrea, Matteo; Gerstmann, Uwe; Schmidt, Wolf Gero; Silberhorn, Christine (CLEO 2023)
We study the interaction of gray tracking and DC ionic conductivity in Potassium Titanyl Phosphate (KTiOPO 4 , KTP) and present a novel way to reduce conductivity via a potassium nitrate treatment improving the device quality.

DC Ionic Conductivity in KTP and Its Isomorphs: Properties, Methods for Suppression, and Its Connection to Gray Tracking - Padberg, Laura; Quiring, Viktor; Bocchini, Adriana; Santandrea, Matteo; Gerstmann, Uwe; Schmidt, Wolf Gero; Silberhorn, Christine; Eigner, Christof (Crystals)
We study the DC conductivity in potassium titanyl phosphate (KTiOPO4, KTP) and its isomorphs KTiOAsO4 (KTA) and Rb1%K99%TiOPO4 (RKTP) and introduce a method by which to reduce the overall ionic conductivity in KTP by a potassium nitrate treatment. Furthermore, we create so-called gray tracking in KTP and investigate the ionic conductivity in theses areas. A local unintended reduction of the ionic conductivity is observed in the gray-tracked regions, which also induce additional optical absorption in the material. We show that a thermal treatment in an oxygen-rich atmosphere removes the gray tracking and brings the ionic conductivity as well as the optical transmission back to the original level. These studies can help to choose the best material and treatment for specific applications.

Electrochemical performance of KTiOAsO_4 (KTA) in potassium-ion batteries from density-functional theory - Bocchini, Adriana; Gerstmann, Uwe; Bartley, Tim; Steinrück, Hans-Georg; Henkel, Gerald; Schmidt, Wolf Gero (Phys. Rev. Materials)

Oxygen vacancies in KTiOPO_4: Optical absorption from hybrid DFT - Bocchini, Adriana; Gerstmann, Uwe; Schmidt, Wolf Gero (Phys. Rev. B)

Potassium titanyl phosphate Z- and Y-cut surfaces from density-functional theory - Neufeld, Sergej; Bocchini, Adriana; Schmidt, Wolf Gero (Physical Review Materials)

Understanding gray track formation in KTP: Ti^3+ centers studied from first principles - Bocchini, Adriana; Eigner, Christof; Silberhorn, Christine; Schmidt, Wolf Gero; Gerstmann, Uwe (Phys. Rev. Materials)

Potassium titanyl phosphate (KTP) quasiparticle energies and optical response - Neufeld, Sergej; Bocchini, Adriana; Gerstmann, Uwe; Schindlmayr, Arno; Schmidt, Wolf Gero (Journal of Physics: Materials)
The KTiOPO4 (KTP) band structure and dielectric function are calculated on various levels of theory starting from density-functional calculations. Within the independent-particle approximation an electronic transport gap of 2.97 eV is obtained that widens to about 5.23 eV when quasiparticle effects are included using the GW approximation. The optical response is shown to be strongly anisotropic due to (i) the slight asymmetry of the TiO6 octahedra in the (001) plane and (ii) their anisotropic distribution along the [001] and [100] directions. In addition, excitonic effects are very important: The solution of the Bethe–Salpeter equation indicates exciton binding energies of the order of 1.5 eV. Calculations that include both quasiparticle and excitonic effects are in good agreement with the measured reflectivity.

Oxygen and potassium vacancies in KTP calculated from first principles - Bocchini, Adriana; Neufeld, Sergej; Gerstmann, Uwe; Schmidt, Wolf Gero (Journal of Physics: Condensed Matter)